The Impact of the COVID-19 Lockdown "Home Quarantine" on the Physical Activity and Lifestyle of Children in Qatar - Nada A. Al-Mulla; Ziyad R. Mahfoud; Ziyad R. Mahfoud (Frontiers Media S.A., 2022)
BackgroundSeveral studies have investigated how the coronavirus disease 2019 (COVID-19) pandemic impacted children's lifestyle. To our knowledge, this is the first study that assesses the impact of quarantine on physical activity, screen time, sleep, and diet in children aged 5 to 12 in Qatar.MethodsCross-sectional data from an online survey distributed in Qatar was analyzed. The survey measured the parents' or caregivers' assessment on the change in the child's physical activity, sleep, screen time, and diet between the two periods (before quarantine and during quarantine). The data was analyzed using frequency distributions, paired t-test and McNemar's test.ResultsData from 144 respondents were analyzed. Due to the quarantine, the total weekly average hours of physical activity significantly decreased with a greatest reduction for the school and after school durations. Only 4.5% of the children were engaging in at least 60 minutes of physical activity per day (in contrast to 25.6% prior to quarantine). The reported barriers for physical activity were screen time for school (52.8%) and leisure (51.4%). There was a significant increase in the total number of main meals per day, with a higher consumption of unhealthy food. The majority of the children had their bedtime and waketime shifted to later because of the quarantine. The parents' or caregivers' satisfaction with the child's lifestyle during quarantine showed that 49.1% were disappointed or very disappointed. Also, 53.8% described their child's mental health as "better before quarantine."ConclusionsQuarantine had a negative impact on the lifestyle of children in Qatar. When implementing restrictions, authorities should consider some interventions to counterpart such impact.